Effectiveness of CBT-Based Group Counseling in Reducing Culture Shock Among College Students - Dhita Azhari Ramadhan; Bau Ratu; Dhevy Puswiartika; Ikhlas Rasido (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aimed to examine the effectiveness of Cognitive Behavioral Therapy (CBT)-based group counseling in reducing culture shock among college students. A quantitative pre-experimental one-group pretest-posttest design was employed. The participants were 12 students selected through purposive sampling based on moderate to high levels of culture shock. Data were collected using a culture shock questionnaire with a reliability coefficient of 0.885 and analyzed with the Wilcoxon Signed-Rank Test. The results showed a significant decrease in culture shock after the intervention, with Z = -3.061 and p = 0.002 (< 0.05). All participants experienced lower scores, and the effect size of r = 0.88 indicated a large effect. These findings confirm that CBT-based group counseling is effective in helping students reduce culture shock through cognitive restructuring, peer support, and the development of adaptive behaviors. The intervention has practical potential for counseling services in higher education to support first-year students’ adjustment, well-being, and academic engagement.